Mapping neurogenesis onset in the optic tectum of Xenopus laevis - Herrgen, L; Akerman, C (Wiley, 2016)
Neural progenitor cells have a central role in the development and evolution of the vertebrate brain. During early brain development, neural progenitors first expand their numbers through repeated proliferative divisions and then begin to exhibit neurogenic divisions. The transparent and experimentally accessible optic tectum of Xenopus laevis is an excellent model system for the study of the cell biology of neurogenesis, but the precise spatial and temporal relationship between proliferative and neurogenic progenitors has not been explored in this system. Here we construct a spatial map of proliferative and neurogenic divisions through lineage tracing of individual progenitors and their progeny. We find a clear spatial separation of proliferative and neurogenic progenitors along the anterior-posterior axis of the optic tectum, with proliferative progenitors located more posteriorly and neurogenic progenitors located more anteriorly. Since individual progenitors are repositioned toward more anterior locations as they mature, this spatial separation likely reflects an increased restriction in the proliferative potential of individual progenitors. We then examined whether the transition from proliferative to neurogenic behavior correlates with cellular properties that have previously been implicated in regulating neurogenesis onset. Our data reveal that the transition from proliferation to neurogenesis is associated with a small change in cleavage plane orientation and a more pronounced change in cell cycle kinetics in a manner reminiscent of observations from mammalian systems. Our findings highlight the potential to use the optic tectum of Xenopus laevis as an accessible system for the study of the cell biology of neurogenesis. This article is protected by copyright. All rights reserved.